2021
DOI: 10.1016/j.ijhm.2020.102719
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 pandemic on domestic tourism: A DEMATEL method analysis on quarantine decisions

Abstract: Highlights Quarantine decisions during a pandemic directly affect the hospitality industry. A DEMATEL method is proposed for quarantine decision due to COVID-19 Pandemic. A real life case study in Turkey is conducted in this paper. Istanbul has an essential impact on the rest of all regions in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 72 publications
3
87
0
4
Order By: Relevance
“…The literature review has shown that political and health crises generate instability and a significant impact on the tourism industry [6,62,63], generating negative effects such as the decrease in visitors that has resulted in low economic income. There is evidence of cases that have gone through similar episodes and have never been able to recover, but there is also evidence of destinations that have applied good strategies and their recovery has been evident [32,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review has shown that political and health crises generate instability and a significant impact on the tourism industry [6,62,63], generating negative effects such as the decrease in visitors that has resulted in low economic income. There is evidence of cases that have gone through similar episodes and have never been able to recover, but there is also evidence of destinations that have applied good strategies and their recovery has been evident [32,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence that the high demand for tourism makes this industry very resilient to a crisis [32]. Currently, in a post-crisis situation, tourists are looking for new forms of tourism that will allow activities with a lower risk of contagion [62]. Given this, the Amazonian area on the border of Ecuador (Sucumbíos) and Colombia (Putumayo) enjoys an advantage and opportunity for a resurgence in terms of nature tourism.…”
Section: Discussionmentioning
confidence: 99%
“…There are few scientific literature sources that would contain comprehensive information on the development of tourism in such conditions. However, the paper of Fatma Altuntas, Mehmet Sahin Gok, 2021 [22] contains a take on further development of the tourism and hospitality sphere in the context of quarantine restrictions.…”
Section: Background and Methodsmentioning
confidence: 99%
“…Step 6: obtain total-relation matrix (TRM) e TRM is obtained using equation (6). is is the matrix obtained as a result of multiplicative inverse of DRM with differences of identity matrix and DRM.…”
Section: (12)mentioning
confidence: 99%
“…Using the DEMATEL, all evaluation criteria are partitioned into two groups, in which the first group is known as cause group and the second group is called as effect group. Owing to these positive features, the DEMATEL has been successfully applied in many recent decision-making problems (see [4][5][6][7]). It is good to note that pairwise comparisons between criteria in DEMATEL are measured using a scale of real numbers accompanied by five linguistic terms.…”
Section: Introductionmentioning
confidence: 99%